Evaluation of cyclic crack resistance of high-carbon steels with different types of cementite mesh (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article investigates the influence of structural constituents of hypereutectoid graphitized steels on the service performance of forming tools with helical calibers. It is shown that complex contact interaction conditions, intensive heat generation, and non-uniform stress distribution lead to accelerated wear and contact fatigue of the roll working surfaces, which imposes increased requirements on the material and its heat treatment regimes.Hypereutectoid steels with different morphologies of the carbide phase and graphite inclusions were experimentally studied under single- and multi-stage normalizing at various temperatures and cooling rates. The regularities of the influence of austenitizing temperature and cooling conditions on carbide refinement, pearlite spheroidization, and the formation of structurally free cementite were established. It was demonstrated that multi-stage normalizing with accelerated cooling ensures enhanced thermal endurance and cyclic crack resistance of the steels.Regression equations were obtained that relate static fracture toughness and thermal endurance to the size of carbide inclusions and the distance between them. On this basis, a scoring scale was developed to assess the influence of the carbide phase on the performance of rolls for ball-rolling mills. It was established that steels with spheroidized pearlite, compact or globular graphite inclusions, and finely dispersed isolated carbides exhibit the best service properties.
Keywords: hypereutectoid steel; graphitization; rolling rolls; thermal endurance; fracture toughness; carbide network; spheroidization